Incidence of exogenous powers in public policies and in the rural sector in Colombia - Londoño, Óscar Cardozo (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This paper analyzes how, throughout Colombian history, a series of forces and powers foreign to the rural sector, have exerted a harmful influence for it. It is studied from different perspectives the impact that these forces and powers have had in detriment to one of the most important sectors for the development of the country, bearing in mind that the rural sector had been predominant in Colombia. Finally, it is made an approach to the current debate on agricultural public policies, from various views, in order to contribute to the study and understanding of the Colombian case.